Anisotropy in multiple ionisation of CO by ion collisions at intermediate interaction strengths. (14th September 2018) - Sharma, Deepak; Bapat, Bhas; Bhatt, Pragya; Safvan, C P
Abstract: Multiple ionisation of the CO molecule following the impact of 100–700 keV He 2+ ions was studied. Fragments arising from the dissociation of CO n + ( n ≤ 5 ) were recorded using the coincidence momentum imaging technique. By measuring the angular distribution of the fragment ions in coincidence, and applying the axial recoil approximation, the angle between the axis of the molecule and the direction of the projectile was determined. Strong anisotropy was observed for high degree of ionisation. The dependence of the anisotropy on the interaction strength and the projectile energy was studied and the results were compared with the predicted values in the literature for diatomic molecules. Furthermore, an asymmetry in the angular distribution owing to the heteronuclear nature of the molecule was observed and quantified, showing that the anisotropy is not entirely a geometric effect as has been presented in earlier works.